NETWORK ELECTRONIC PLATFORMS AS A MEANS INFORMATION SYSTEM OF EDUCATIONAL FOR PUPILS MINOR ACADEMY OF SCIENCES OF UKRAINE - Demianenko, В.Б. (Journal of Information Technologies in Education (ITE), 2012)
The methodological problems of forming of the computer-based learning system by facilities of ICT are considered, in particular an application of network services in research activity of students of the Minor Academy of Sciences of Ukraine are described in the article.